2016
DOI: 10.3389/fmicb.2016.01730
|View full text |Cite
|
Sign up to set email alerts
|

Low-Concentration Ciprofloxacin Selects Plasmid-Mediated Quinolone Resistance Encoding Genes and Affects Bacterial Taxa in Soil Containing Manure

Abstract: The spread of antimicrobial resistance in environment is promoted at least in part by the inappropriate use of antibiotics in animals and humans. The present study was designed to investigate the impact of different concentrations of ciprofloxacin in soil containing manure on the development of plasmid-mediated quinolone resistance (PMQR) – encoding genes and the abundance of soil bacterial communities. For these studies, high-throughput next-generation sequencing of 16S rRNA, real-time polymerase chain reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Two possible explanations are suggested to account for the significant enrichment of these genera under the pressure of enrofloxacin treatment. Firstly, several previous studies reported that Lactococcus , Burkholderia and Bacillus were associated with intrinsic ciprofloxacin resistance ( Mathur and Singh, 2005 ; Fajardo et al, 2008 ; Walsh and Duffy, 2013 ; Huang et al, 2016 ). Secondly, resistant mutant might be selected under the antibiotic pressure and lead to the propagation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two possible explanations are suggested to account for the significant enrichment of these genera under the pressure of enrofloxacin treatment. Firstly, several previous studies reported that Lactococcus , Burkholderia and Bacillus were associated with intrinsic ciprofloxacin resistance ( Mathur and Singh, 2005 ; Fajardo et al, 2008 ; Walsh and Duffy, 2013 ; Huang et al, 2016 ). Secondly, resistant mutant might be selected under the antibiotic pressure and lead to the propagation.…”
Section: Discussionmentioning
confidence: 99%
“… Videnska et al (2013) reported that Enterococcus in the chicken fecal microbiota was increased in response to the single or repeated therapy with tetracycline and streptomycin. Lower concentrations of ciprofloxacin in soil also enriched the genus Enterococcus ( Huang et al, 2016 ) Enterococcus has shown to be intrinsically resistant to several antibiotics, such as β-lactams and aminoglycosides. The emergence of virulent Enterococcus that is resistant to vancomycin (VRE) has widely raised public concern.…”
Section: Discussionmentioning
confidence: 99%
“…However, the rate of spread of ARGs depends on the antibiotic concentration in the soil. Huang et al ( 2016 ) showed that the dissipation rate of plasmid-located genes [i.e., qnrS, oqxA, aac(6 ′ )-Ib-cr ] was significantly lower in soil treated with ciprofloxacin at concentrations of 0.04 and 0.4 mg/kg soil compared to soil treated with antibiotic at 4 mg/kg and controls. Forsberg et al ( 2012 ) also found little evidence for HGT in soil.…”
Section: Diversity Of Antimicrobial Resistance Genesmentioning
confidence: 99%
“…This has been seen for quinolone resistance since PMQR genes have become prevalent in clinical and environmental settings. 133,146,[157][158][159][160][161][162][163][164] One of PMQR genes that have emerged rapidly in these settings are qnr genes incurring fitness advantages in the presence of fluoroquinolones. It has been shown through biochemical assays that Qnr proteins can reduce the amount of enzyme-DNA targets for ciprofloxacin inhibition.…”
Section: Qnr Prevalencementioning
confidence: 99%